Host Immune-Metabolic Adaptations Upon Mycobacterial Infections and Associated Co-Morbidities - Llibre, Alba; Dedicoat, Martin; Burel, Julie G.; Demangel, Caroline; O’Shea, Matthew K.; Mauro, Claudio (Frontiers in Immunology, 2021)
Mycobacterial diseases are a major public health challenge. Their causative agents include, in order of impact, members of the Mycobacterium tuberculosis complex (causing tuberculosis), Mycobacterium leprae (causing leprosy), and non-tuberculous mycobacterial pathogens including Mycobacterium ulcerans. Macrophages are mycobacterial targets and they play an essential role in the host immune response to mycobacteria. This review aims to provide a comprehensive understanding of the immune-metabolic adaptations of the macrophage to mycobacterial infections. This metabolic rewiring involves changes in glycolysis and oxidative metabolism, as well as in the use of fatty acids and that of metals such as iron, zinc and copper. The macrophage metabolic adaptations result in changes in intracellular metabolites, which can post-translationally modify proteins including histones, with potential for shaping the epigenetic landscape. This review will also cover how critical tuberculosis co-morbidities such as smoking, diabetes and HIV infection shape host metabolic responses and impact disease outcome. Finally, we will explore how the immune-metabolic knowledge gained in the last decades can be harnessed towards the design of novel diagnostic and therapeutic tools, as well as vaccines.